Lenin as a Child Visual Propaganda and Pedagogy - Somogyvári, Lajos (Acta Paedagogica Vilnensia, 2019)
My study aims to reveal the connections between visual propaganda and pedagogy during the Hungarian state-socialism by analyzing different variations of a single picture of Vladimir Lenin. The ideological indoctrination played an important role in the socialization of children, even teachers; thus, the communist power tried to create a new ceremonial-ritual order and a socialist identity. The following analyzed images (photos and paintings) show different functions and meanings; by reframing and transforming photographs and contexts, we can demonstrate how the viewers could have been manipulated. The starting photo comes from my studies (based upon the corpus of Hungarian pedagogical journals) published in 1970, showing a seemingly unconventional representation: Lenin as a child.
Keywords: visual propaganda; history of education; pedagogical journals; Lenin Cult; communist education